Nekateri vidiki spolnega nasilja nad ženskami v Kraljevini Jugoslaviji v luči civilnega in kazenskega prava - Bajc, Gorazd (Studia Historica Slovenica, 2024)
This work deals with the status of women in the Kingdom of Yugoslavia in the period between 1929 and 1941, in the perspective of civil and criminal law. Civil law, unlike criminal law, was not unified during the existence of the Kingdom. Thus, in the light of civil law, women throughout the Kingdom enjoyed different rights. Rights and social status depended on the civil code in use in a certain area. While women were well protected in the light of criminal law, a study of sexual violence against women carried out in the Maribor Regional Archives showed that case law was not uniform.
Keywords: civil code; civil law; civilni zakonik; civilno pravo; criminal code; criminal law; družbeni položaj žensk; kazenski zakonik; kazensko pravo; Kingdom of Yugoslavia; Kraljevina Jugoslavija; sexual violence; social position of women; spolno nasilje